First principle calculations of core-level binding energy and Auger kinetic energy shifts in metallic solids - Olovsson, Weine; Marten, Tobias; Holmström, Erik; Johansson, Börje; Abrikosov, Igor A. (Journal of electron spectroscopy and related phenomena, 2010)
We present a brief overview of recent theoretical studies of the core-level binding energy shift (CLS) in solid metallic materials. The focus is on first principles calculations using the complete screening picture, which incorporates the initial (ground state) and final (core-ionized) state contributions of the electron photoemission process in X-ray photoelectron spectroscopy (XPS), all within density functional theory (DFT). Considering substitutionally disordered binary alloys, we demonstrate that on the one hand CLS depend on average conditions, such as volume and overall composition, while on the other hand they are sensitive to the specific local atomic environment. The possibility of employing layer resolved shifts as a tool for characterizing interface quality in fully embedded thin films is also discussed, with examples for CuNi systems. An extension of the complete screening picture to core–core–core Auger transitions is given, and new results for the influence of local environment effects on Auger kinetic energy shifts in fcc AgPd are presented.